NIR-responsive bio-system with sequential antibacterial and immunomodulatory effects for the treatment of periodontitis - Xinyi Qiu; Wanping Wang; Chenying Shen; Yue Zhao; Xiao Song; Yijun Yu; Chao Liu; Wenlei Wu; Leiying Miao; Shuangshuang Ren (Bioactive Materials, 2025)
In periodontitis, the recurrent bacteria plaque adheres, and intracellular bacteria survival leads to inflammatory immune disorder in periodontal tissue and makes clinical therapeutic outcomes unpredictable. Thoroughly clearing of plaque biofilm and intracellular infectious agents and then regulating the immune environment is a sequential therapy that can match the characteristics of periodontitis. Herein, we construct a near-infrared (NIR)-responsive drug delivery system Hemin@ER-IR808, and investigated its sequential antibacterial and immunomodulatory effects as well as the mechanism in vitro and in vivo. According to the results, NIR laser activated IR808 to produce reactive oxygen species (ROS) to inhibit the proliferation of periodontal bacteria and disrupt the biofilm structure. Then ROS opened the erythrocyte (ER) membrane to release the encapsulated Hemin, which activated the ferroptosis-like stress of intracellular bacteria. Mechanistically, at the early stage of intracellular bacterial infection, Hemin@ER-IR808 ehanced the glycolysis, metabolic reprogramming macrophage to M1-type, which limited the number of intracellular bacteria more than the M2-type; later increased the mitophagy and the level of GPX4, SLC7A11 and HO-1, protecting the macrophage from ferroptosis. In vivo, Hemin@ER-IR808 reduced the number of periodontal flora in rats and alleviated periodontal inflammation. At the later stage, Hemin@ER-IR808 exerted antioxidant effect and promoted the repair of periodontal tissue. In the complex periodontal infectious and inflammatory organizational environment, Hemin@ER-IR808 can emerge as a viable strategy to protect periodontal tissue from reinfection and exert immunomodulatory function to achieve sequential periodontal tissue regeneration.